Monitoring of the "Energiewende": Energy efficiency indicators for Germany - Barbara Schlomann; Matthias Reuter; Bruno Lapillonne; Karine Pollier; Jan Rosenow (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
The increasing number of energy and climate targets both at national and international level induces a rising demand for regular monitoring. In this paper, we analyse the possibilities and limits of using energy efficiency indicators as a tool for monitoring these targets. We refer to the energy efficiency targets of the German Energiewende and calculate and discuss several energy efficiency indicators for Germany both at the level of the overall economy and the main energy consumption sectors. We make use of the energy efficiency indicator toolbox that we have developed within the ODYSSEE database in recent years and find that there is still a considerable gap to close to achieve the overall energy efficiency targets in Germany by 2020. We also show that progress in energy efficiency slowed down between 2008 and 2012, i.e. compared to the base year of most of the German energy efficiency targets and find that energy efficiency progress in the industrial sector during the last decade has been especially slow. We conclude that improvements in energy efficiency have to speed up considerably in order to achieve the targets for 2020. Although the use of energy efficiency indicators is limited by data constraints and some methodological problems, these indicators give a deep insight into the factors determining energy consumption and can therefore complement the official monitoring process of the German Energiewende which only relies on highly aggregated indicators for energy efficiency.
urn:nbn:de:0011-n-2977908
Keywords: 330; energy efficiency targets; target monitoring; energy efficiency indicators; decomposition analysis; German "Energiewende"